Sejarah Pengembangan Organisasi Pendidikan Islam di Indonesia - Eva Athifah; Muhamad Ihsan Khuluki; Beta Hikmah Zahrotunnisa (Pusat Riset dan Inovasi Nasional, 2026)
This study traces the history of the development of Islamic educational organizations in Indonesia from the pre-colonial period to the Reformation era using a descriptive qualitative approach through a literature review. The findings indicate that Islamic education developed gradually, beginning with informal institutions centered around mosques and pesantren, and later responding to colonial pressures with the emergence of organizations such as Muhammadiyah and Nahdlatul Ulama. This development continued through the formal recognition of madrasahs during the independence era, modernization under the New Order regime, and more dynamic institutional transformations during the Reform era. Amid various challenges such as educational dualism, resource constraints, and the threat of extremism, Islamic educational organizations continue to innovate by integrating religious and general knowledge without abandoning their Islamic identity. This study affirms that Islamic educational organizations are the primary foundation for building a character-based national education system.